2020
DOI: 10.1038/s41598-020-72517-2
|View full text |Cite
|
Sign up to set email alerts
|

Direct visualization of the extracellular binding structure of E-cadherins in liquid

Abstract: E-cadherin is a key Ca-dependent cell adhesion molecule, which is expressed on many cell surfaces and involved in cell morphogenesis, embryonic development, EMT, etc. The fusion protein E-cad-Fc consists of the extracellular domain of E-cadherin and the IgG Fc domain. On plates coated with this chimeric protein, ES/iPS cells are cultivated particularly well and induced to differentiate. The cells adhere to the plate via E-cad-Fc in the presence of Ca2+ and detach by a chelating agent. For the purpose of clarif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…S-shaped conformations of desmosomal cadherins have been previously studied by electron tomography ( 41 , 42 ), supporting the existence of the S-shaped dimers of E-cadherin in the classical cadherins observed in this study. With conventional AFM, however, only the W-shaped dimer has been reported in the E-cadherin–Fc fusion protein, and the relationship to the dimeric structures seen in the crystal and dynamics of the W-shaped dimer have not been fully investigated ( 43 ). In the previous study, the S-shaped and X-like dimers observed by our HS-AFM may have been disrupted on mica substrates using conventional AFM due to conformational constraints on the mica substrates by Fc conjugation, which artificially connects two cadherins at the membrane-proximal sides of the ectodomains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S-shaped conformations of desmosomal cadherins have been previously studied by electron tomography ( 41 , 42 ), supporting the existence of the S-shaped dimers of E-cadherin in the classical cadherins observed in this study. With conventional AFM, however, only the W-shaped dimer has been reported in the E-cadherin–Fc fusion protein, and the relationship to the dimeric structures seen in the crystal and dynamics of the W-shaped dimer have not been fully investigated ( 43 ). In the previous study, the S-shaped and X-like dimers observed by our HS-AFM may have been disrupted on mica substrates using conventional AFM due to conformational constraints on the mica substrates by Fc conjugation, which artificially connects two cadherins at the membrane-proximal sides of the ectodomains.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, the S-shaped and X-like dimers observed by our HS-AFM may have been disrupted on mica substrates using conventional AFM due to conformational constraints on the mica substrates by Fc conjugation, which artificially connects two cadherins at the membrane-proximal sides of the ectodomains. A strong adsorption of proteins on the mica substrates using the hydrophobic coating of the substrates for low-speed imaging (∼3 min per frame) ( 43 ) also could have disrupted the S-shaped and X-like dimers. Multiple dimeric structures and the structural dynamics of cadherin while maintaining dimeric bonds demonstrate that our high-speed imaging (0.2 to 0.4 s per frame) was minimally invasive for cadherin dimers.…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin is an adhesion molecule, which is of great significance for maintaining the normal morphology and complete structure of epithelial cells. When its expression decreases, it will accelerate the metastasis of tumor cells [ 20 ]; β -catenin and E -cadherin play a synergistic role and are highly expressed in noninvasive or normal cells [ 21 ]; vimentin is an intermediate fibrous protein. The high expression of vimentin protein makes tumor cells more aggressive, and its increased expression in tumor cells is a sign of the occurrence of EMT [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cadherins usually operate in a homotypic fashion, though they can also adhere heterotrophically [23] (Figure 1A). The extracellular binding region of members of the cadherin family consists of 5 extracellular calcium (EC1-EC5) dependent repeat regions that allow for strong binding, mainly facilitated by EC1 and EC2 [24]. They gain their adherence strength via an intracellular structural region, which binds to actin filaments in the cell.…”
Section: The Cadherin Family Mediating Cell-cell Attachmentmentioning
confidence: 99%